The influence of rhinitis on bronchial asthma – the prognosis of application of glycocorticosteroids on treatment schemas - Samoliński, Bolesław; Komorowski, Jarosław (Przewodnik Lekarza/Guide for GPs, 2006)
There is enough evidence of an epidemiological, aetiological and physiopathological link between chronic rhinitis (usually allergic) and asthma. Some studies have demonstrated that treatment of chronic rhinitis produces a benefit in the evolution of asthma when both diseases co-occur in the same patient, which suggests a therapeutic link. However, it is less clear whether rhinitis is a direct trigger for asthma or the two conditions are simply manifestations of a common underlying process. Evidence for a role for rhinitis as a trigger for asthma includes many examples of improvement in asthma once concomitant rhinitis is treated. Possible mechanisms for this relationship include naso-pharyngo-bronchial reflexes, postnasal drip, abnormal breathing, and the local production of inflammatory mediators that trigger pulmonary inflammation. On the other hand, evidence exists that rhinitis and asthma are manifestations of a common process. For example, there are similarities between the histopathological changes in the epithelium in chronic rhinitis and asthma. The aim of this paper is to highlight the importance of co-treatment of rhinitis coexisting with asthma.